Development of a seismograph using piezoelectric sensors in Arduino platform - de Amorim, Cleber Alexandre [UNESP] (2021)
Since 2018, the theoretical deepening of the physics component - in the area of Natural Sciences and its Technologies - is subdivided into the following thematic units of knowledge: matter and energy; life, Earth and cosmos; technology and scientific language. In this context, the teaching of physics must have as one of its pillars, in contemporary society, the search for explanations about new technologies integrated into the student's life, profession and daily life, supported by the inseparability between theory and practice in the teaching-learning process. This article aims to highlight the potential of articulating physics education, subsidized by projects and practice, with the contribution of technologies. This work exposes three experimental tests about the seismograph to be applied in the context of the classroom. It is proposed to outline a tool that acts as a laboratory in the classroom, helping teachers and students in a better assimilation of concepts in Natural Sciences and its Technologies, in order to provide them with demonstrations and scientific experiments that lead them to decisions in the light of science and scientific knowledge.